THE BENEFICIAL ROLE OF ANTI-PHOSPHOLIPASE A2 RECEPTOR AUTO-ANTIBODIES AND RITUXIMAB IN THE MANAGEMENT OF RECURRENT PRIMARY MEMBRANOUS NEPHROPATHY AFTER KIDNEY TRANSPLANTATION - Nosheen Anjum; Zahid Nabi (Journal of Ayub Medical College Abbottabad, 2021)
Background: Recurrence of the primary kidney disease causing graft loss in an otherwise good functioning graft in post renal transplantation period is a well-known entity. Approximately 15% of the graft failure occurs secondary to recurrence of the primary glomerulonephritis in post renal transplant period. Regarding primary glomerulonephritis, almost 33-35% of patients suffering from primary membranous nephropathy (PMN), an organ specific auto-immune podocytopathy reach end stage renal disease (ESRD) and renal transplant is then the only treatment modality of choice for them. But, unfortunately 30-50% will experience the disease recurrence and 40-50% will end up with graft loss. The discovery of M-type anti phospholipase auto antibodies (APLA2R-ab) has changed the paradigm. Different remarkable studies are available in the literature that have concluded that APLA2R-ab titers if performed before the renal transplantation are helpful in predicting the disease recurrence and their titration in post-renal transplant period is clinically relevant to see the risk of disease recurrence and its progression, help in treatment monitoring and also to observe the treatment response in terms of complete or partial remission of the disease. Till now, there are no evidence-based guidelines available for the prevention of rPMN in post renal transplant period. The traditional treatment regimens beneficial for the management of PMN in native kidneys are associated with certain serious side effects in post renal transplant period. Rituximab, an anti-CD20 monoclonal antibody (anti CD20 mAb) has emerged as a promising treatment option for such patients. Conclusion: In conclusion an approach intending an early diagnosis of the rPMN by using the APLA2r levels in serum and its management by utilizing rituximab has proved worthy in minimizing the risk of allograft loss secondary to recurrence of PMN in post renal transplant period. However further studies are still awaited regarding the efficacy, dose and duration of the treatment.